Specific Hsp100 Chaperones Determine the Fate of the First Enzyme of the Plastidial Isoprenoid Pathway for Either Refolding or Degradation by the Stromal Clp Protease in Arabidopsis - Pulido, Pablo; Llamas, Ernesto; Llorente, Briardo; Ventura, Salvador; Wright, Louwrance P.; Rodríguez-Concepción, Manuel (PLoS genetics, 2016)
The lifespan and activity of proteins depend on protein quality control systems formed by chaperones and proteases that ensure correct protein folding and prevent the formation of toxic aggregates. We previously found that the Arabidopsis thaliana J-protein J20 delivers inactive (misfolded) forms of the plastidial enzyme deoxyxylulose 5-phosphate synthase (DXS) to the Hsp70 chaperone for either proper folding or degradation. Here we show that the fate of Hsp70-bound DXS depends on pathways involving specific Hsp100 chaperones. Analysis of individual mutants for the four Hsp100 chaperones present in Arabidopsis chloroplasts showed increased levels of DXS proteins (but not transcripts) only in those defective in ClpC1 or ClpB3. However, the accumulated enzyme was active in the clpc1 mutant but inactive in clpb3 plants. Genetic evidence indicated that ClpC chaperones might be required for the unfolding of J20-delivered DXS protein coupled to degradation by the Clp protease. By contrast, biochemical and genetic approaches confirmed that Hsp70 and ClpB3 chaperones interact to collaborate in the refolding and activation of DXS. We conclude that specific J-proteins and Hsp100 chaperones act together with Hsp70 to recognize and deliver DXS to either reactivation (via ClpB3) or removal (via ClpC1) depending on the physiological status of the plastid.